2006
DOI: 10.1097/01.gme.0000196812.96128.e8
|View full text |Cite
|
Sign up to set email alerts
|

The importance of continued exercise participation in quality of life and psychological well-being in previously inactive postmenopausal women

Abstract: Healthy postmenopausal women gain significant psychological benefit from moderate-intensity exercise. However, exercise participation must continue to maintain improvements in psychological well-being and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
36
0
6

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 29 publications
4
36
0
6
Order By: Relevance
“…The most negative scores on the psychological dimension were for feelings of anxiety, nervousness, and depression. Our findings in this area are also consistent with the results of similar studies (17,25,(37)(38)(39).…”
Section: Discussionsupporting
confidence: 93%
“…The most negative scores on the psychological dimension were for feelings of anxiety, nervousness, and depression. Our findings in this area are also consistent with the results of similar studies (17,25,(37)(38)(39).…”
Section: Discussionsupporting
confidence: 93%
“…In adults, studies have reported significant positive associations between current PA and most SF-36 domains in healthy general populations for both genders and across all age groups [45][46][47][48], indicating the importance of regular PA for HRQL as well as for objective health measures and disease prevention [48]. It is possible that only current PA levels impact HRQL: A randomized controlled trial previously showed that while participation in a PA program lead to improvements in both physical and mental HRQL, these improvements were maintained only if exercise participation continued [49]. Current adult PA was a significant positive covariate for several SF-36 outcomes in the PALS sample.…”
Section: Discussionmentioning
confidence: 94%
“…Em relação ao tipo de atividade, cinco estudos analisaram atividade física por caminhada (Asbury, et al, 2006;Daley, et al, 2007;Elavsky, 2009;Elavsky & McAuley, 2005;McAndrew, et al, 2009), sendo que três destes também analisaram a prática do Yoga (Elavsky, 2009;Elavsky & McAuley, 2005, os outros verificaram o nível de atividade física através de questionário. Nota-se uma necessidade em estudar outros tipos de atividade física, visto que existem poucos estudos que comparam o contraste de diferentes tipos de atividade e exercícios físicos para avaliar o efeito dos sintomas de mulheres na menopausa (Teoman, Ozcan, & Acar, 2004).…”
Section: Discussionunclassified
“…Quanto aos demais estudos analisados nesta revisão, todos (Asbury, et al, 2006;Daley, et al, 2007;Elavsky, 2009;Elavsky & McAuley, 2005McAndrew, et al, 2009;Mirzaiinjmabadi, Anderson, & Barnes, 2006;Moilanen, et al, 2012;Nelson, et al, 2008), concordaram que a atividade física promove melhorias em relação aos sintomas psicológicos durante a menopausa, eis que os resultados destes estudos apresentaram redução da ansiedade, do estresse, diminuição dos sintomas depressivos, da preocupação com a saúde e do medo de ficar doente, além disso, verificaram também aumento do bem-estar e da qualidade de vida.…”
Section: Discussionunclassified
See 1 more Smart Citation